“Quem te ensinou a brincar?” o aprendizado na Associação Cultural de Capoeira Angola Comunidade - Rodrigues, Juliana Carmen Brito (2011)
The aim of this thesis is to describe the dynamic of functioning of the Associação Cultural de Capoeira Angola Comunidade, which is a group of capoeira angola in the neighborhood called Bairro dos Novais, located on the periphery of João Pessoa (PB), focusing on an attempt to identify how the learning process works in that context. The continuous interest in learning by capoeira players (capoeiristas) is directly connected with the strong presence of hierarchy, respect and discipline, which are strengthened, especially within the capoeira roda. Social relations between capoeiristas – children and adults – and their activities, especially within the roda, as well as during this group‟s annual Festival, contribute to the learning process, in that Association, as significantly as the teachings passed on by master Naldinho (which is founder and chairman), through his teaching methodology of capoeira angola.